Regions and the world economy the coming shape of global production, competition, and political order - Scott, Allen John. (Oxford Oxford University Press, 2000)
One of the shifts that is occurring in the world as we enter the 21st century is the increasing openness and interpretation of national economies and sovereign states. This text explores the economic logic and political meaning of these developments.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Economic geography; Regional economics; International economic relations; Competition, International